건강신념 모델에 근거한 보육시설 유아대상 영양교육 프로그램 개발 및 적용 - 신은경(Eun Kyung Sin); 이연경(Yeon Kyung Lee) (Korean journal of community nutrition, 2006)
The purpose of this study was to develop various nutrition education materials, including an animated CD, for day care center children and their teachers and in order to apply the nutrition education programs systematically. We evaluated the effect of the nutrition education programs on nutrition knowledge in the first year, and the effect of the nutrition education programs on nutrition knowledge, food attitudes and eating behaviors in the second year in day care center children. In the first year, nutrition education foundational materials, such as the animated CD-ROM, videotape, textbook, panels, posters, slogans, leaflets, picture disks, hand puppets, stickers for compensation and poster boards were developed. The subjects were 537 children (286 boys,251 girls) aged four to six years. In the second year, nutrition education materials, such as the animated CD-ROM and textbook were developed. The nutrition education group included 368 children (177 boys 191 girls) aged four to six years, and the comparison group consisted of 108 children (54 boys,54 girls) Regarding the nutrition knowledge test results in the first year, the pre-test mean of children was 6.82, however, the post-test mean was 11.35 and showed a significant increase (p < 0.001). Regarding the nutrition knowledge test and the food attitude test results in the second yew, the nutrition education group had significantly higher scores than the comparison group in a post-test (p < 0.001). For the eating behavior test results, the post-test means between the comparison group and the nutrition education group were not significant. The test results show that several months of nutrition education is not enough to improve eating behaviors. As a result, nutrition education has improved nutrition knowledge and food attitudes in day care center children but short-term nutrition education was not sufficient to induce a change in eating behaviors. To improve eating behaviors in day care center children, nutrition education programs must be applied to day care center children in addition to their Parents and Persistent education will have to be continued.